Improved codal recommendations for design of RC dog-legged stairs supported on transverse landing edges - Menon, Devdas; Sivaraman, K. V.; Janardhana, Maganti (Journal of Structural Engineering, 2025)
This paper highlights a shortcoming in the IS 456 and BS 8110 recommendations for simplified analysis of reinforced concrete (RC) dog-legged stairs supported on transverse landing edges. Based on a comprehensive study using finite element analysis with plate-shell elements, and a limited experimental study, it is established that the landing-going junctions of such stairs offer translational and rotational restraints, hitherto neglected in simplified analysis. The resulting distribution of bending moments is significantly different from the one traditionally adopted in design practice. Recommendations are proposed in this paper for making the design more rational and economical.